Disaster and Emergency Preparedness : Activity Guide for K to 6th Grade Teachers - International Finance Corporation (World Bank, Washington, DC, 2014)
Communities around the world are faced with natural hazards-extreme environmental events such as floods, cyclones, earthquakes, fires, and tsunamis. For some communities, these natural hazards turn into disasters, resulting in tremendous losses and injuries for students, school staff and families. However, by taking preventative measures before hazard impact, and learning preparedness and response, a culture of safety can be fostered. Communities can reduce and even eliminate such losses. This booklet offers suggestions for a range of classroom and community activities to teach elementary school students, from kindergarten to sixth grade, about natural and man-made hazards, how to protect oneself and respond to them, and how to help reduce their impact and prevent them from becoming community disasters. The booklet is divided into five sections on classroom and community activities: 1) hazards and disasters in our community; 2) measuring our environment; 3) disaster prevention; 4) emergency response; and 5) promoting disaster prevention in your community.